Hyperbranched poly(triazole) with thermal and metal ion dual stimuli-responsiveness1. Issue 26 (14th July 2015) - Wu, Jianhua; Liu, Wenmei; Han, Huijing; Sun, Ruyi; Xie, Meiran; Liao, Xiaojuan
<x xml:space="preserve">Abstract</x> Hyperbranched poly(triazole) bearing oligo(ethylene glycol) terminal groups is dual stimuli-responsive to thermal conditions and metal ions and is capable for the selective absorption of Ag+ ion on tuning temperature.